2023
DOI: 10.3390/jfb14020060
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Cellulose/Cellulose Imidazolium Bio-Hybrid Membranes for In Vitro and Antimicrobial Applications

Abstract: In biomedical applications, bacterial cellulose (BC) is widely used because of its cytocompatibility, high mechanical properties, and ultrafine nanofibrillar structure. However, biomedical use of neat BC is often limited due to its lack of antimicrobial properties. In the current article, we proposed a novel technique for preparing cationic BC hydrogel through in situ incorporation of cationic water-soluble cellulose derivative, cellulose bearing imidazolium tosylate function group (Cell-IMD), in the media use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 55 publications
2
7
0
Order By: Relevance
“…Due to its fibrous and porous nature, BC mimics the structure of Extracellular Matrix (ECM) thus aiding in the adhesion and proliferation of cells. Salama et al [67] and Qui et al [68] also have reported excellent cytocompatibility of pristine BC with L929 cells. After 96 hours of incubation, pristine BC continued to show higher proliferative rate than the control.…”
Section: Biocompatibilitymentioning
confidence: 93%
See 1 more Smart Citation
“…Due to its fibrous and porous nature, BC mimics the structure of Extracellular Matrix (ECM) thus aiding in the adhesion and proliferation of cells. Salama et al [67] and Qui et al [68] also have reported excellent cytocompatibility of pristine BC with L929 cells. After 96 hours of incubation, pristine BC continued to show higher proliferative rate than the control.…”
Section: Biocompatibilitymentioning
confidence: 93%
“…Due to its fibrous and porous nature, BC mimics the structure of Extracellular Matrix (ECM) thus aiding in the adhesion and proliferation of cells. Salama et al [67] . and Qui et al [68] .…”
Section: X‐ray Diffraction (Xrd)mentioning
confidence: 97%
“…In our experiments, the three species were similarly affected either by Fe 3 O 4 -Ag or Fe 3 O 4 -Au nanoparticles (Figure 7). Since the cell wall is the first structure to establish contact with the environment and with the host, it is important to stress the importance of the data obtained with Candida regarding that the cell wall is similar in composition (glucans, mannans, or chitin), but the architecture is different, changing in this way the interaction with the host [54,55]. On the other hand, regarding the fungicide effect of Fe3O4 particles in eukaryotic cells, it is important to mention the fact that three Candida species were tested: C. albicans, C. parapsilosis, and C. glabrata, all human-life-threatening pathogens due to the high morbidity and mortality [52,53].…”
Section: Antibacterial and Antifungal Activity Assaymentioning
confidence: 99%
“…In our experiments, the three species were similarly affected either by Fe3O4-Ag or Fe3O4-Au nanoparticles (Figure 7). Since the cell wall is the first structure to establish contact with the environment and with the host, it is important to stress the importance of the data obtained with Candida regarding that the cell wall is similar in composition (glucans, mannans, or chitin), but the architecture is different, changing in this way the interaction with the host [54,55]. Nevertheless, prokaryotic or eukaryotic cells were not affected by the presence of magnetite nanoparticles since no growth inhibition was observed (data not shown), suggesting that the antibiotic effect observed was due to the action of metallic ions or to the interaction between magnetite and the metal.…”
Section: Antibacterial and Antifungal Activity Assaymentioning
confidence: 99%
“…Cellulose macrofibres are composed of microfibrils formed from nanofibrils with a crystalline part and an amorphous part in a row. Cellulose nanocrystals (CNCs) and nanofibers (CNFs) have been used as alternative green and bioactive fillers in a broad field of innovative nanostructured materials [ 13 , 14 , 15 , 16 ]. Lignin is the second most abundant biopolymer intimately intertwined with hemicellulose, forming a matrix surrounding the ordinated cellulose microfibrils.…”
Section: Green and Bio-sustainable Materialsmentioning
confidence: 99%